Design for maintenance accessibility using BIM tools. Issue 3 (2014) - ,; ,
Abstract : Purpose – The purpose of this paper is to investigate the design for maintenance accessibility (DFMA) method, and the opportunities offered by the application of building information modeling (BIM) software to accomplish this design.Design/methodology/approach – In this paper definitions of DFMA are investigated, different BIM tools including Solibri Model Checker (SMC) and Revit Add‐in are explored for maintainability problems. Microsoft Visual Studio is used as a tool to develop Add‐in applications in Revit for DFMA problem. A case study involving exhaust fan maintenance accessibility is used to validate the proposed solution.Findings – Maintenance accessibility tends to be ignored in the design phase. The process of clash detection among building components does not ordinarily detect accessibility issues. SMC can help partially solve this problem if there is a corresponding SMC rule sets available. As a 3D modeling tool associated with a parametric database of components, Revit offers opportunities for designers to explore the background geometry and parametric database to add more functions in the form of Add‐in applications which can help facilities managers anticipate and solve maintenance accessibility issues.Research limitations/implications – The add‐in tools developed for this paper and the rules used for SMC are specific for the case study. A more general and comprehensive tool or rule set will be the direction for a future study.Practical implications – This study shows that maintainability checking is possible in the design phase. Comprehensive maintainability checking in the design phase would result in a big savings in maintenance cost during a facility's lifecycle.Originality/value – The paper illustrates with a case study using two different tools the process of accessibility checking for maintenance in the design phase, which transforms the concept of "design for maintenance accessibility" into reality.